Efisiensi belanja administrasi pemerintah Kota Palembang: Pendekatan Stochastic Frontier Analysis - Ririn Puji Astuti; M. Syirod Saleh; Muhammad Subardin (Department of Development Economics, Universitas Sriwijaya, 2017)
This study aims to find out the efficiency of the administration of Palembang City, 2002 – 2016 period in building the area with and components that caused whether or not administrative expenditure of an area was efficient. This study uses data secondary data that is realization data of administrative expenditure, average employe’s expenditure, capital expenditure and local revenue. This data was tested by stochastic frontier analysis (SFA). The results of estimation from the stochastic frontier analysis (SFA) found that the administrative expenditure of the city of Palembang was inefficiency. The average variable of employee expenditure has a negative related and has a significant effect to administration costs in Palembang City. The relationship of variable capital expenditure with the administration costs of the regional government in the city of Palembang has a positive and significant effect. And the Local Revenue variables have a positive and significant effect to administration costs in Palembang City.